Isoeugenol monooxygenase characterization and whole-cell bioconversion systems towards vanillin production from plant-derived precursor isoeugenol - Nunes, Francisco Quintas (2020)
Tese de mestrado, Microbiologia Aplicada, Universidade de Lisboa, Faculdade de Ciências, 2019